2006
DOI: 10.1111/j.1600-0609.2005.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐mediated lysis of autologous platelets in chronic idiopathic thrombocytopenic purpura

Abstract: Our findings suggest that CTLs are activated in chronic ITP and might be involved in the pathogenesis of this disorder. Apoptosis and perforin/granzyme-mediated cytotoxicity constitute an important pathway through which CTLs destruct autologous platelets. CTLs might be a reasonable target for a therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 16 publications
9
113
0
2
Order By: Relevance
“…20,21 In the present study, the supernatant concentrations and messenger RNA (mRNA) expression of granzyme A, granzyme B, and perforin were measured. Consistent with our previous study, 16 granzyme B and perforin were increased in the cytotoxic group compared with healthy controls. When IL-27 was added, a significant reduction in granzyme B expression was observed in the cytotoxic group, whereas no difference was observed in granzyme A or perforin ( Figure 2B-C).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…20,21 In the present study, the supernatant concentrations and messenger RNA (mRNA) expression of granzyme A, granzyme B, and perforin were measured. Consistent with our previous study, 16 granzyme B and perforin were increased in the cytotoxic group compared with healthy controls. When IL-27 was added, a significant reduction in granzyme B expression was observed in the cytotoxic group, whereas no difference was observed in granzyme A or perforin ( Figure 2B-C).…”
Section: Resultssupporting
confidence: 81%
“…[2][3][4][5]13,16 In this study, the normal range of CTL-induced platelet apoptosis was established from the mean 6 2 standard deviations of results in healthy controls. The patients with CTL-induced platelet apoptosis higher than the upper limit of normal range were assigned to the cytotoxic group (23 patients); otherwise, they were assigned to the noncytotoxic group (15 patients) ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The results confirmed our former finding that increasing cytotoxic T lymphocyte-mediated platelet lysis was the predominant cause of thrombocytopenia in ITP patients without platelet autoantibodies. 9,10 In addition, we also found rhBAFF could increase the production of IFN-␥ but had no obvious effect on the secretion of IL-4 in in vitro experiments, consistent with earlier studies showing typical Th1-mediated responses and reduced Th2-mediated responses in BAFF transgenic mice. 16 ITP is a heterogeneous disease; besides humoral immune abnormalities, several T-cell abnormalities have been demonstrated in patients with ITP, including Th1 bias, the inhibition of autologous megakaryocyte apoptosis by CD8 ϩ T cells, and cell-mediated cytotoxic lysis of platelets by CTLs.…”
Section: Discussionsupporting
confidence: 78%
“…16 ITP is a heterogeneous disease; besides humoral immune abnormalities, several T-cell abnormalities have been demonstrated in patients with ITP, including Th1 bias, the inhibition of autologous megakaryocyte apoptosis by CD8 ϩ T cells, and cell-mediated cytotoxic lysis of platelets by CTLs. 3,4,[8][9][10]35 Our results indicated that elevated BAFF not only was involved in humoral immune abnormalities by promoting the survival of B cells, but also may be involved in the cellular immunity abnormalities by promoting the survival of T cells.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation